Consolidated Good Practices in Education and Child Labour : Education as an Intervention Strategy to Eliminate and Prevent Child Labour. - Office, International Labour (International Labour Office, 2007)
This book presents some of the most important good practices identified by ILO-IPEC from thousands of projects and programmes around the world. It shows a first step towards sharing the considerable portfolio of knowledge and expertise (amassed by ILO-IPEC)in using education as a principal means of combating child labour and in linking the elimination of child labour to the Education For All initiative.